Inovasi Rasa dan Kemasan Penganan Tradisional Opak Khas Bojongkunci, Pameungpeuk, Jawa Barat sebagai Upaya Inovatif Menuju Pemasaran Global - Mukhlishah; Amelia, Nina; Junaedi Ramadhan, Enjang (Bayani, 2023)
Opak is a traditional food made from rice flour, or glutinous rice, and is popular among Sundanese people. However, with the growing variety of foods and the trend of trying foreign foods, traditional foods such as opak are becoming less popular. To combat this, the authors propose innovative strategies such as changing the size of the opak to make it more portable and efficient, introducing new flavors to attract consumers, and updating the packaging to make it more attractive. This innovation aims to preserve and promote opak as  traditional Indonesian food on the global market.